1997
DOI: 10.1038/nm0197-73
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and delayed degeneration after spinal cord injury in rats and monkeys

Abstract: Apoptosis is a morphologically defined form of programmed cell death seen in a variety of circumstances, including immune cell selection, carcinogenesis and development. Apoptosis has very recently been seen after ischemic or traumatic injury to the central nervous system (CNS), suggesting that active cell death as well as passive necrosis may mediate damage after CNS injury. After spinal cord injury (SCI) in the rat, typical post-traumatic necrosis occurred, but in addition, apoptotic cells were found from 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
728
5
9

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,051 publications
(784 citation statements)
references
References 21 publications
33
728
5
9
Order By: Relevance
“…Apoptotic cells, including oligodendrocytes were found from 6 h to 3 weeks after injury, especially in the white matter of the spinal cord. 4 These cells could be responsible for axonal demyelination and further functional impairment. 3,4,9 Considering the protective e ects of the energy precursor creatine on metabolically stressed neural cells in vitro, 18 it is likely that higher intracellular energy levels reached after creatine supplementation in vivo may have saved some of these cells in the penumbra zone around the primary lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptotic cells, including oligodendrocytes were found from 6 h to 3 weeks after injury, especially in the white matter of the spinal cord. 4 These cells could be responsible for axonal demyelination and further functional impairment. 3,4,9 Considering the protective e ects of the energy precursor creatine on metabolically stressed neural cells in vitro, 18 it is likely that higher intracellular energy levels reached after creatine supplementation in vivo may have saved some of these cells in the penumbra zone around the primary lesion.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 ± 7 The early phase of secondary tissue destruction a ects neuronal as well as glial cell populations. 2,4,8,9 Later, a dense gliotic scar develops, inhibiting axon regeneration in addition to the endogenously present myelinassociated neurite growth inhibitory constituents. 2,10 Although di erent glial cells participate in the scar formation, the reactive astrocytes play a predominant role re¯ected by the very high levels of glial acid ®brillary protein (GFAP).…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian apoptotic cell death programme is regulated by the caspase family of cysteine proteases. 16,41,80,82 In particular, downstream caspase-3 has been shown to be important to neuronal development and injury by inducing fragmentation of nuclear DNA in vitro and in vivo. 83,114 Additional control of cell death/survival is provided by the mammalian antiapoptotic proteins Bcl-X L and Bcl-2.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Apoptosis is an actively regulated response that occurs after various cells have been subjected to external or internal stimuli. Recent experimental studies and clinical observations have revealed that spinal cord lesions are greatly exacerbated by apo ptosis 10,12,13,15,18,19,[22][23][24] . However, the molecular and cellular mechanism of apoptosis is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%